Motivations of Share Buybacks in India - Kaur, Karamjeet (Indian Journal of Finance, 2012)
Majority of the studies on share buybacks have been undertaken in the developed countries, especially the U.S. As the Indian capital market has unique features, it is desirable to examine the motivations of Indian share buybacks. A total of 119 events of share buybacks were analyzed over a period of 2003 - 2010. Public announcements provided by the companies were studied to identify the major reasons provided by the companies for undertaking share buybacks. The results reveal that the main motivations for announcing share buy backs in India are: Improving financial performance and returning of surplus cash. There is no shift in motivations across time and methods.